2014
DOI: 10.1182/blood-2014-02-554980
|View full text |Cite
|
Sign up to set email alerts
|

Platelets are required for enhanced activation of the endothelium and fibrinogen in a mouse thrombosis model of APS

Abstract: • The anti-b2GP1 autoantibody/ b2GP1 complex binds to the platelet thrombus, amplifying platelet activation.• Platelets are required for enhanced activation of the endothelium and fibrin generation by the anti-b2GP1 autoantibody/b2GP1 complex.Antiphospholipid syndrome (APS) is defined by thrombosis, fetal loss, and the presence of antiphospholipid antibodies, including anti-b2-glycoprotein-1 autoantibodies (antib2GP1) that have a direct role in the pathogenesis of thrombosis in vivo. The cellular targets of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
93
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 57 publications
0
93
0
1
Order By: Relevance
“…Quantitative results are presented for the median fluorescence associated with platelets and fibrin from multiple thrombi in each group ( Figure 1B-C Although the defect in platelet accumulation was expected on the basis of the absence of platelet dense granules, thus confirming previous studies demonstrating diminished platelet thrombi in ruby-eye mice in response to vessel wall injury, 22 the defect in fibrin generation was unanticipated. The absence of fibrin generation cannot be explained by the absence of platelet accumulation because we have previously shown normal fibrin formation in Par4 2/2 mice in whom platelets cannot be thrombin activated 23 ; in WT mice treated with eptifibatide, an inhibitor that blocks platelet accumulation 15,24 ; and in chimeric mice lacking platelet b3 integrins. 17 In contrast, there is no fibrin generation in b3 2/2 mice lacking both platelet aIIbb3 and endothelial aVb3.…”
Section: Thrombus Formation Is Defective In Hps6mentioning
confidence: 99%
“…Quantitative results are presented for the median fluorescence associated with platelets and fibrin from multiple thrombi in each group ( Figure 1B-C Although the defect in platelet accumulation was expected on the basis of the absence of platelet dense granules, thus confirming previous studies demonstrating diminished platelet thrombi in ruby-eye mice in response to vessel wall injury, 22 the defect in fibrin generation was unanticipated. The absence of fibrin generation cannot be explained by the absence of platelet accumulation because we have previously shown normal fibrin formation in Par4 2/2 mice in whom platelets cannot be thrombin activated 23 ; in WT mice treated with eptifibatide, an inhibitor that blocks platelet accumulation 15,24 ; and in chimeric mice lacking platelet b3 integrins. 17 In contrast, there is no fibrin generation in b3 2/2 mice lacking both platelet aIIbb3 and endothelial aVb3.…”
Section: Thrombus Formation Is Defective In Hps6mentioning
confidence: 99%
“…Finally, we felt that our recently described animal model was particularly amenable to assessing the role of neutrophil adhesion in antiphospholipid antibody-mediated thrombosis (21). Notably, the majority of models used to study APS in mice have relied on explicit vessel wall damage such as femoral vein pinch injury (13,54), laser injury to the cremaster microcirculation (55,56), and ferric chloride application (57). The flow restriction model used by our While the PSGL-1 -/-mice used here are global KOs, we added specificity to the model with adoptive transfer experiments.…”
Section: Discussionmentioning
confidence: 99%
“…55,56 Conversely, a recent study suggested that activation of platelets by aPL antibodies is associated with thrombosis formation. 57 In these ways, aPL antibodies seem to be a major contributor to the pathogenesis of APS. [6][7][8][9] HLA class II expression is induced on endothelial cells after exposure to cytokines such as IFN-g and TNF-a.…”
mentioning
confidence: 99%